(3LhGgQ GdYbOjf aj aVd GdTQajf TQa GdYde GdLdj hGdfSH GdYdjs - (3Ydj Hf YHO Gddg Hf CMeO GdMSfj GdSeghOj GdeOfj GdTGaYj ,CHh GdMSf fhQ GdOjf,J (B911 (3g` s ((3YHO GdQMef Hf Ydi GdMSjfi GdSeghOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR ChdjGAg CYdGe GdOjf CeG HYO , aEf Gddg JYGdi bO ENJU YHGOg Cgd GdYde GdSfi , hCgd GdHjJ GdfHhi s
(3BNQgG (B:s
(3Udi Ydjg GdgfG hYdjge hGdUMH eG EMVQJ QHG CafGf hgPG eG jSQ Gddg JYGdi LeYg hJCdjag s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B307 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B74s
Keywords: (3GdJGQjNs